The Frustrating Realities of Cold Climate Design:: Piercing the Skin: Ins-U-lation versus Ins-O-lation - Meyer Boake, Terri (ARCC Conference Repository, 2019)
The first principle of energy efficient environmental building design for a cold climate is as follows: First INSULATE, and then INSOLATE. The use of passive solar design principles can be key to reducing the overall amount of energy consumed by residential buildings. Create warm tight walls, then, perforate with an adequate number of windows to absorb free energy. Ensure that there is adequate thermal mass present to absorb and then, later, reradiate the free heat. The principle is simple. Its detailed application is complex. Apertures effectively puncture the building skin, resulting in a discontinuity of the thermal integrity of the envelope. Piercing creates a thermal hiatus, as the thermal resistance of the windows is normally a fraction of the insulation value of the wall. Environmental concerns arise out of the loss of heat through these openings as well as the control of solar gain as it affects cooling loads. Orientation must be intrinsically considered for each and every opening. Shading devices need to be designed in order to manage the amount and quality of solar gain and light. Daylighting should also factor into the design equation, in its potential to reduce energy costs as well as a "D”esign element.